A Survey of Documentary Materials Available on U.S. Tribal Websites. Issue 1 (2nd April 2016) - Seikel, Michele
ABSTRACT: This survey of official U.S. tribal websites examined sites for documentary materials of importance to each tribe that have been archived online, including such materials as historical essays, photos, videos, maps, newspapers, legal and historical documents, historical images, books, pamphlets, bibliographies, cultural and language materials. The materials found on those websites appear to be intended for the use of both tribal members and the general public. The result of the survey was to show that many of the same types of documentary materials held in tribal archives are also available on official websites, and to produce a current snapshot of the large array of tribal records which have been made openly available, although the length of time each document will be available on each site is unknown.